Peer Influence As The Dominant Factor In Coffee Drink Consumption Among Non-Health Major University Of Indonesia Students In 2023 - Patrisha Ramadhiani; Triyanti Triyanti; Sandra Fikawati (Indonesian Journal of Public Health Nutrition (IJPHN), 2023)
Coffee drinks are sugar-sweetened beverages made from coffee powder, sugar, and water, through a heating process. High consumption of coffee drinks is associated with the sugar content, which can increase the risk of obesity. The aim of this study was to determine the differences in coffee drinks consumption levels based on individual characteristics and environmental factors among non-health undergraduate students at the University of Indonesia in 2023. This quantitative study used a cross-sectional design with a sample of 181 active undergraduate non-health students in 2023. Data were collected in June 2023 through self-administered. The results showed that 52.5% of the respondents had a high level of coffee drink consumption (≥ 3-4 times per week). Bivariate analysis revealed significant differences in coffee drinks consumption based on smoking behavior, peer influence, availability of coffee at home, and accessibility (p-value < 0.05). Multivariate analysis indicated that peer influence was the dominant factor influencing students' coffee drink consumption. The researchers suggest students increase their awareness and encourage their social circle to limit excessive coffee consumption. Additionally, relevant health institutions are advised to provide education, increase information about recommended limits of coffee consumption.